2022
DOI: 10.1007/s11356-022-20625-z
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of plant species suitability in green walls based on API, heavy metal accumulation, and particulate matter capture capacity

Abstract: Today, one of the most pressing issues confronting the civilized and modern world is air pollution.Particulate matter (PM) is a well-known pollutant that contributes signi cantly to urban air pollution and has numerous short-and long-term adverse effects on human health. One method of reducing air pollution is to create green spaces, mainly green walls, as a short-term solution. The current study investigated the ability of nine plant species to reduce tra c-related PM using a green wall system installed along… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 70 publications
0
12
0
Order By: Relevance
“…Wax-like foliar accumulation in P. guajava and C. citrinus (Fig. 3 n and p) act as a transpiration inhibitor, which justifies the increase in water content at the polluted site (Banerjee et al 2022 ; Hozhabralsadat et al 2022 ). At the control site, the clear and open stomata along with guard cells and linear striations can be seen at the epidermis of P. guajava and C. citrinus .…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…Wax-like foliar accumulation in P. guajava and C. citrinus (Fig. 3 n and p) act as a transpiration inhibitor, which justifies the increase in water content at the polluted site (Banerjee et al 2022 ; Hozhabralsadat et al 2022 ). At the control site, the clear and open stomata along with guard cells and linear striations can be seen at the epidermis of P. guajava and C. citrinus .…”
Section: Resultsmentioning
confidence: 93%
“…In this investigation, relatively fewer stomata were observed for A. indica and T. ciliate in comparison to C. citrinus and P. guajava . A study by Hozhabralsadat et al ( 2022 ) found that the plants with low stomatal density have high potential retention of fine particles. In the present study, the stomatal density and trichomes were more in the polluted site as compared to the control site.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Water's ability to capture pollutants in the air [5] and the air-purifying attributes of green vegetation constitute additional advantages conferred by the implementation of systems aimed at advancing the United Nations Sustainable Development Goals (SDGs) [6][7][8][9][10][11][12][13][14][15][16]. By integrating fog harvesting technology into green wall systems, the overall sustainability of these structures is enhanced.…”
Section: Introductionmentioning
confidence: 99%